Stranger in a Strange Land: Biotechnology and the Federal Circuit - Lawrence M. Sung (Washington University Journal of Law & Policy, 2000)
This Article surveys recent Federal Circuit decisions regarding biotechnology-related subject matter from the combined perspectives of science and the law.
Keywords: Biotechnology; Patent law; United States. Court of Appeals for the Federal Circuit; United States. Patent and Trademark Office